Centennial analysis in tropical cyclone-induced precipitation in Korea - Minhee Chang; Chang-Hoi Ho; Junho Ho; Eun-Jeong Cha (Weather and Climate Extremes, 2023)
Tropical cyclone (TC)-induced precipitation has undergone significant multidecadal changes over the last 117 years (1904–2020) on the Korean Peninsula, as determined through the analysis of affected TCs and surface-observed precipitation at ten stations in the Republic of Korea (hereafter Korea). Information on TCs that have affected Korea over a century was collected from the National Typhoon Center of the Korea Meteorological Administration (KMA). The information was cross-validated by referring to the International Best Track Archive for Climate Stewardship archive, while the information for 1904–1950 was cross-validated by also examining extreme weather reports in newspapers. A significant regime shift in the annual total heavy rainfall (confined to rain events ≥100 mm day−1), and its frequency associated with the affected TCs was found before and after 1979. The regime-shift signal is robust regardless of the methodology. Heavy rainfall from non-TC events, however, has presented a regime-shift increase since 1997. Based on a detailed review of historical documents describing instrument type, measuring method, altitude, and site location, this rainfall increase in regime-shift is likely a non-climatic signal coming from updates in measurement tools (i.e., the weather station automation project of KMA) during 1995–2000. However, increases in heavy rainfall of TC events in 1979 are comprehensively supported by the intensity and track changes in Korea affecting TC and changes in large-scale atmospheric and oceanic environments. The present results provide an earnest validation of TC records over the Korean Peninsula and confirm a regime-shift increase in TC hazards over Korea, thus providing grounds for further global analysis.